Primary empathy deficits in frontotemporal dementia - Baez, Sandra; Manes, Facundo; Huepe, David; Torralva, Teresa; Fiorentino, Natalia; Richter, Fabian; Huepe-Artigas, Daniela; Ferrari, Jesica; Montañes, Patricia; Reyes, Pablo; Matallana, Diana; Vigliecca, Nora S.; et al. (Frontiers in Aging Neuroscience, 2014)
Loss of empathy is an early central symptom and diagnostic criterion of the behavioral variant frontotemporal dementia (bvFTD). Although changes in empathy are evident and strongly affect the social functioning of bvFTD patients, few studies have directly investigated this issue by means of experimental paradigms. The current study assessed multiple components of empathy (affective, cognitive and moral) in bvFTD patients. We also explored whether the loss of empathy constitutes a primary deficit of bvFTD or whether it is explained by impairments in executive functions (EF) or other social cognition domains. Thirty-seven bvFTD patients with early/mild stages of the disease and 30 healthy control participants were assessed with a task that involves the perception of intentional and accidental harm. Participants were also evaluated on emotion recognition, theory of mind (ToM), social norms knowledge and several EF domains. BvFTD patients presented deficits in affective, cognitive and moral aspects of empathy. However, empathic concern was the only aspect primarily affected in bvFTD that was neither related nor explained by deficits in EF or other social cognition domains. Deficits in the cognitive and moral aspects of empathy seem to depend on EF, emotion recognition and ToM. Our findings highlight the importance of using tasks depicting real-life social scenarios because of their greater sensitivity in the assessment of bvFTD. Moreover, our results contribute to the understanding of primary and intrinsic empathy deficits of bvFTD and have important theoretical and clinical implications.